Identity Crisis in Bedi’s “Lajwanti”: An Exploration of Cultural Trauma through Gendered Violence (Saptagandaki Journal, 2025)
The Partition of India unlocked religious and communal violence throughout the country, leaving unspeakable agony and a legacy of colonialism for the tormented survivors and their descendants. This cataclysmic event compelled it to pay the price for its independence by tearing its own motherland’s breast into two parts. The parted earth’s stayers and their progenies have not yet been emancipated from the anguish of division due to the shadow of trauma. During this time, mostly women were sexually used and abused to destroy the enemy’s power and respect since they were the biological reproducers of the collectivity and transmitters of its culture. Researchers generally focus on the visible reasons to calculate the damage caused by the conflict. However, they ignore how socially constructed subject matters also play a significant role in deteriorating the situation of women. Against this backdrop, this paper explores how the protagonist of Bedi’s story, “Lajwanti”, experiences an identity crisis due to the socially constructed truth and double-yoked gendered and communal violence during the partition and post-partition period. It examines the literary text through the lens of cultural trauma as a theoretical tool based on the central characters’ traumatic experiences endowed by the society, the violence inflicted on the female bodies, sexuality by the opposite religious groups, and identity crisis in the primary character of the story. This study reveals that socially interceded truth frolics in damaging the victimized women’s honor more than the heinous act of sexual violence in the conflict. It helps to comprehend how the unproductive human clash of the diverse religious groups affected by communally fabricated truth creates great trouble with an identity crisis for the victims.